Development of genetic manipulation tools for Pseudomonas oleovorans - Ke, Hongjiao; Zhang, Zhichao; Liu, Yan; Luo, Quan; Lu, Xuefeng (Frontiers in Microbiology, 2025)
Due to the robust capabilities in hydrocarbon/herbicide degradation, biopolymer/compatible solute synthesis, steroid bioconversion, and zinc salt solubilization, Pseudomonas oleovorans has shown considerable potential for industrial, agricultural, and environmental applications. However, the poor availability of genetic tools for this bacterium hinders genetic, biochemical, metabolic, and engineering studies. In the present study, a genetic manipulation system that is based on electroporation was established for P. oleovorans strain T9AD. Antibiotic susceptibility profiling demonstrated that aminoglycoside-type antibiotics, such as kanamycin and gentamycin, are suitable selective markers. Optimization of electroporation parameters, including processing temperature for competent cell preparation, DNA concentration, DNA-cell pre-incubation, and post-pulse recovery, yielded stable electroporation efficiencies at levels of 104 CFU/μg DNA. Among five candidate genomic neutral sites, two were experimentally verified and exhibited favorable suitability for gene integration. Integration of reporter genes at these sites did not affect cell growth, salt tolerance, and compatible solute anabolism. Using these neutral sites or the broad-host-range plasmid pBBR1MCS-5, regulated gene expression via the genome- or plasmid-based strategies was successfully achieved. All together, these tools, in combination with established conjugation methods, set up a robust technological platform to facilitate fundamental and application research in P. oleovorans.